Effects of Sitagliptin on Lipid Profile in Patients With Type 2 Diabetes Mellitus After 7 Years of Therapy. (26th May 2019) - Derosa, Giuseppe; Tritto, Isabella; Romano, Davide; D'Angelo, Angela; Catena, Gabriele; Maffioli, Pamela
Abstract: The aim of this study was to investigate whether the effects of sitagliptin on lipid profile were maintained even after 7 years of treatment. We treated 591 patients who had not been well controlled by current therapy with the addition of sitagliptin 100 mg/d. Data were compared with those of 612 patients treated with sulfonylureas plus metformin, pioglitazone plus metformin, and pioglitazone plus sulfonylureas. We observed that, compared with patients treated with sulfonylureas plus metformin, patients receiving sitagliptin in addition to metformin experienced a greater decrease of total cholesterol and low‐density lipoprotein cholesterol (LDL‐C) compared with baseline and with sulfonylureas plus metformin. Compared with patients treated with metformin plus pioglitazone, sitagliptin resulted in a greater reduction of total cholesterol and LDL‐C relative to baseline and to metformin plus pioglitazone. We also observed a higher increase of high‐density lipoprotein cholesterol (HDL‐C) after sitagliptin had been added to pioglitazone, both compared with baseline and to the competitor. Compared with patients treated with pioglitazone plus sulfonylureas, the combination of sitagliptin and sulfonylureas was more effective in reducing LDL‐C and in increasing HDL‐C. High‐sensitivity C‐reactive protein was decreased by all pharmacological combinations. We can conclude that the addition of sitagliptin led to a better and more durable improvement of lipid profile compared with sulfonylureas or thiazolidinediones.